Academic Services Based on Minimal Service Standards at AMI Makassar Maritime Polytechnic - Nur, Muhammad; Musa, Andi Ernie Zaenab; Harifuddin, Harifuddin; Zainuddin, Rasyidah (SCAD Independent, 2023)
This study aimed to describe the efficiency of implementing academic services and the effectiveness of educational services based on minimum service standards. This quantitative descriptive study used a survey approach with AMI Maritim Makassar Polytechnic students. Data collection techniques included observations, interviews, and documentation studies. The data analysis technique used frequency tabulation with percentage calculation and a Likert scale measuring instrument. The findings revealed that implementing the minimum standard service was “simple”, with a Likert scale category score of 91.66%, and the “on time” variable had a score of 85%. The variable “openness” had a score of 97.5%. The “effectiveness” variable had a score of 96.6%. The variable “Indiscriminate” had a score of 97.5%. The “efficiency” variable had a 72.5% score. Implementation of academic services based on “Minimum Service Standards” with simple indicators such as “timely, open, not discriminant, efficient, and economical” was categorized as “satisfactory”, and the level of satisfaction with academic services based on the “Minimum Service Standards” among the students was classified as “strongly effective”.